2019
DOI: 10.1016/j.jare.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress and hydroxyectoine enhance phosphate solubilisation and plant colonisation capacity of Kosakonia radicincitans

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
4
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 62 publications
1
8
4
5
Order By: Relevance
“…Los controles fueron analizados bajo las mismas condiciones experimentales. La actividad enzimática (U) se definió como microgramos de PNP liberado por mililitro por hora (µg/mL/h) (Barrera et al, 2019).…”
Section: Determinación De La Actividad Fosfatasas áCidasunclassified
“…Los controles fueron analizados bajo las mismas condiciones experimentales. La actividad enzimática (U) se definió como microgramos de PNP liberado por mililitro por hora (µg/mL/h) (Barrera et al, 2019).…”
Section: Determinación De La Actividad Fosfatasas áCidasunclassified
“…For instance, Schubert et al (2007) reported that the introduction of ectoine genes of a halophylic bacterium Chromohalobacter salexigens into a non-halophilic bacterium Escherichia coli leads to abundant synthesis of ectoine by this recombinant strain. Barrera et al (2019) showed that hydroxyectoine similarly to salt stress increases the solubility of phosphates and plant colonization capacity of Kosakonia radicincitans. Additionally, Lai et al (2014) demonstrated enhanced tolerance to drought and salt stresses in transgenic Arabidopsis expressing glycine betaine from halophilic methanarcheon Methanophilus portucalensis.…”
Section: Relationship Between Chemical Structure and Activity Of Compmentioning
confidence: 99%
“…Annunziata et al (2019);Barrera et al (2019); Che-Othman et al(2020); Ferreira et al (2015b); Hossain et al (2017); Iqbal et al (2015); Jawahar et al (2019); Kurepin et al (2015); Lai et al (2014); Maimaiti et al (2016); Majumdar et al (2016); Meena et al (2019); Panuszko et al (2016); Ramos-Ruiz et al (2019); Rejeb et al (2014); Shevyakova et al (2013); Singh et al (2017); Suprasanna et al (2016); Vicente et al (2016) (continued)…”
mentioning
confidence: 99%
“…In certain cases, such as in banana (Musa acuminata) plantation, the inoculation of banana with Bacillus amyloliquefaciens and Pseudomonas fluorescens resulted in improved plant growth and altered the metabolome profile of the plant [2]. It was also observed that halotolerant bacteria Kosakonia radicincitans increased root-colonising capability and improved growth of radish plant [3]. The use plant growth promoting rhizobacteria, Bacillus subtilis, B. amyloliqufaciens, B. cereus, Pseudomonas putida, and P. fluorescens, were also shown to reduce the damage of tomato root by nematode [4].…”
Section: Introductionmentioning
confidence: 99%